Changes in egg production, egg quality and egg nutritional values of laying hens in response to dietary supplementation with green tea water extracts. Issue 1 (31st December 2022) - Xia, Bing; Liu, Jun; Sun, Da; Liu, Ya-Li; Liu, Donghong
ABSTRACT: Our previous studies demonstrated that low-grade tea had some beneficial effects on egg production performance and egg quality. Extracts derived from low-grade tea had high levels of active ingredients. Thus, this study investigated the effects of green tea water extracts (GTWE) supplementation on egg production, egg quality and egg nutritional value of laying hens. A total of 192 laying hens were randomly allotted to four groups T0, T1, T2 and T3, which fed with basal diet supplemented with 0%, 0.3%, 0.5% and 1.0% GTWE, respectively. Results showed that 0.3% GTWE supplementation increased egg production and improved feed conversion ratio significantly, while 0.5% and 1.0% GTWE supplementation resulted in no significant effects. Furthermore, 1.0% GTWE had adverse effects on feed intake. GTWE treatment improved egg quality, as shown by the increased albumen height and Haugh unit. At the same time, GTWE treatment improved the egg nutritional value, as presented by the increased content of vitamin E and lecithin. On the other hand, GTWE treatment decreased cholesterol, triglyceride, and malonaldehyde levels. However, the strength and thickness of eggshell were negatively affected. The comprehensive analysis suggested low dose of GTWE could be used to developing a desired functional feed supplement.